Upaya Pengendalian DBD Hasil Evaluasi Survey Mawas Diri Di Rw 2 Kelurahan Tenggilis Mejoyo Kecamatan Tenggilis Mejoyo - Muhammad Kalaznykov; Meiriyanti Dhita; Maliku Nurrochman Widandi; Manata Wijaya Sasmita; Maulana Muchammad Aunun Najib; Mentari Nata Kusuma; Michael Bramantya; Michelle Madeline Maydavania; Made Ayu Mira Cyntia Dewi; Made Peni Juliana; Izzah Al Nabilah; Adiwinoto, Ronald Pratama (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2023)
The Self-Introduction Survey (SMD) is an activity for identifying, collecting, and assessing people's health. It is carried out by cadres and local community leaders under the guidance of the Kelurahan/Kelurahan head and health officers. The aim of the study was to identify problems in controlling dengue hemorrhagic fever (DHF), the underlying factors, and alternative solutions to DHF control problems in RW 02, Tenggilis Mejoyo Village. A descriptive research method with a cross-sectional study was used. Data collection was carried out by a self-introduction survey (SMD), and respondents were interviewed using a questionnaire instrument. The respondents were 20 Great Surabaya Cadres (KSH). DHF control priority issues were prepared using the CARL method, and causative factor analysis was done using a fish bone Ishikawa diagram. The study found that most of the KSH in the RW 02 area of Tenggilis Mejoyo Village were aged between 25 and 60 years and had a bachelor's degree. The most common health problem was DHF, caused by cadres' lack of knowledge and inappropriate behavior in eradicating mosquito larvae nests (PSJN). The alternative solutions to the problem were proposing regular additions of cadres according to their area and providing the widest possible opportunity for cadres to obtain information regarding PSJN properly through counseling. The chosen problem-solving method was to provide counseling to KSH. The SMD activity carried out in RW 02 Tenggilis Mejoyo Village identified DHF as the priority health problem. Counseling on KSH was selected as the follow-up problem-solving method, which was in line with the findings in the field, namely the need for additional information regarding DHF knowledge and appropriate behavior in PSJN.